(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Lazarenko G. A. Artistic and aesthetic taste of preschool children and especially its manifestation. In research questions of features of display of artly-esteticheskogo taste of children senior preschool age are revealed, namely: emotional reactions, requirement for perception fine, features of perception of surrounding and musical sounds. As it is revealed, that помагают to be shown to hudozhesvenno-aesthetic taste is musical-theatrical activity, performing and creative activity of preschool children.